In Defense of Intuitions - Chapman, A. author. aut Link
VII, 427 p.
Keywords: A reply to contemporary skepticism about intuitions and a priori knowledge, and a defense of neo-rationalism from a contemporary Kantian standpoint, focusing on the theory of rational intuitions and on solving the two core problems of justifying and explaining them.